2007
DOI: 10.1371/journal.pbio.0050065
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal Ganglion Cells Can Rapidly Change Polarity from Off to On

Abstract: Retinal ganglion cells are commonly classified as On-center or Off-center depending on whether they are excited predominantly by brightening or dimming within the receptive field. Here we report that many ganglion cells in the salamander retina can switch from one response type to the other, depending on stimulus events far from the receptive field. Specifically, a shift of the peripheral image—as produced by a rapid eye movement—causes a brief transition in visual sensitivity from Off-type to On-type for appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 52 publications
5
134
0
Order By: Relevance
“…6 -8) changes in the relative strength of input from ON and OFF pathways in the receptive field center mediate the observed luminance-dependent transitions. Similar changes in convergent ON and OFF input were shown to transiently switch contrast preference (OFF pref to ON pref ) in a subset of salamander RGCs after a saccadelike stimulus (Geffen et al 2007). How ON and OFF pathways converge onto Sw1-, Sw2-, and Sw3-RGCs and how the balance of these convergent inputs shifts as a function of luminance remain to be determined and will likely follow morphological and/or genetic identification of the respective cell types.…”
Section: Discussionmentioning
confidence: 84%
“…6 -8) changes in the relative strength of input from ON and OFF pathways in the receptive field center mediate the observed luminance-dependent transitions. Similar changes in convergent ON and OFF input were shown to transiently switch contrast preference (OFF pref to ON pref ) in a subset of salamander RGCs after a saccadelike stimulus (Geffen et al 2007). How ON and OFF pathways converge onto Sw1-, Sw2-, and Sw3-RGCs and how the balance of these convergent inputs shifts as a function of luminance remain to be determined and will likely follow morphological and/or genetic identification of the respective cell types.…”
Section: Discussionmentioning
confidence: 84%
“…The internal functional architecture of our models match that of the retina at the level of individual neurons, and moreover our models generalize from natural scenes, but not white noise, to a wide range of artificially structured stimuli with vastly different statistics. Thus this work provides quantitative validation for the deep learning approach to neuroscience in an experimentally accessible sensory circuit, places decades of work [7][8][9][10][11][12][13][14][15] on retinal responses to artificially structured stimuli on much firmer foundations of ethological relevance, and highlights the fundamental importance of studying sensory circuit responses to natural stimuli.…”
mentioning
confidence: 79%
“…3E), frequency doubling in response to reversing gratings 14 (Fig. 3F) and polarity reversal 15 (Fig. 3G).…”
Section: Cnns Replicate Wide Range Of Retinal Phenomenamentioning
confidence: 95%
“…Selective reshaping could account for repulsive effects of the surround on orientation tuning in V1 (Sillito et al, 1995), the repulsion of orientation tuning observed in cross-orientation suppression (Kabara and Bonds, 2001), or the switch from OFF to ON response properties in salamander RGC cells when the polarity of the surround is reversed (Geffen et al, 2007). More generally, the feedforward weights are constantly reshaped by competition with other objects in the scene (Fig.…”
Section: Reshaping Of Sensory Responses By the Surroundmentioning
confidence: 99%
“…However, receptive fields are not invariant but depend drastically on which measurement methods and stimuli are used (Theunissen et al, 2000;Blake and Merzenich, 2002;Carandini et al, 2005), on stimulus strength (Moore et al, 1999;Sceniak et al, 1999;Sutter, 2000;Solomon et al, 2006;), and on stimuli outside the receptive field that do not elicit responses by themselves (Blakemore and Tobin, 1972;Maffei and Fiorentini, 1976;Sillito et al, 1995;Brosch and Schreiner, 1997;Geffen et al, 2007). This non-invariance is due to a collection of nonlinear effects including adaptation (Dragoi et al, 2000;Schwartz et al, 2007), divisive inhibition (Carandini and Heeger, 1994), saliency effects (Sillito et al, 1995), surround suppression (Brosch and Schreiner, 1997;Freeman et al, 2001), and surround facilitation (Polat et al, 1998).…”
Section: Introductionmentioning
confidence: 99%